1990
DOI: 10.1099/00221287-136-3-481
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Immunological Comparison of Lipopolysaccharides from Bordetella Species

Abstract: Lipopolysaccharides (LPS) isolated fromacid, glucosamine, uronic acid, phosphate and fatty acids. The fatty acids C14 : 0, C16 : 0 and POHC14 : 0 were common to all the LPS preparations. LPS from B. pertussis strains additionally contained i d 1 6 : 0, those from B. parapertussis contained isoCl4 : 0 and isoC16 : 0, and those from B. bronchiseptica contained C16:l. By SDS-PAGE, LPS from B.perfussis had two bands of low molecular mass, and the LPS from B. parapertussis and B. bronchiseptica showed low molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
23
0
3

Year Published

1992
1992
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 23 publications
2
23
0
3
Order By: Relevance
“…bronchiseptica LPS induces greater inflammatory responses in vitro than LPSs from B. pertussis and B. parapertussis. Previous studies have reported differences in the biological and immunological properties of LPSs of the three Bordetella species (1,48,49), and the results of our infection experiments suggest that B. bronchiseptica induces a greater inflammatory response via TLR4 than B. pertussis or B. parapertussis. These results suggest that there may be differences in the ability of each LPS to induce TLR4-dependent responses.…”
Section: Resultssupporting
confidence: 58%
“…bronchiseptica LPS induces greater inflammatory responses in vitro than LPSs from B. pertussis and B. parapertussis. Previous studies have reported differences in the biological and immunological properties of LPSs of the three Bordetella species (1,48,49), and the results of our infection experiments suggest that B. bronchiseptica induces a greater inflammatory response via TLR4 than B. pertussis or B. parapertussis. These results suggest that there may be differences in the ability of each LPS to induce TLR4-dependent responses.…”
Section: Resultssupporting
confidence: 58%
“…The presence of the correct mutation in the bvgS gene on the chromosome was confirmed by nucleotide sequencing in both directions after obtaining the gene by PCR. The correct phenotype was confirmed by testing colonies for hemolytic activity on Bordet-Gengou agar supplemented with 15% defibrinated sheep blood and 50 mM MgSO 4 . Neisseria meningitidis was grown at 37°C on GC agar plates (Oxoid) supplemented with Vitox (Oxoid).…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that Bordetella LPS is highly immunogenic, acts as an immunological adjuvant, and exhibits the properties that are expected of an endotoxin (4,12,61). Furthermore, Bordetella LPS and its recognition by the TLR4/ MD-2 complex have been shown to be important determinants for the course of infection in mice (6,32,33).…”
mentioning
confidence: 99%
“…Its endotoxin, an immunomodulator of the bacterial surface, has been antigenically defined and the structures of the constituent lipopolysaccharides (LPS) established (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). B. parapertussis, the other agent of whooping cough is not a strictly human pathogen and can often be isolated from late-stage pertussis patients as well as from infected sheep (6,9,12,13).…”
mentioning
confidence: 99%